Աշխատուժի օգտագործման արդյունավետությունը ձեռնարկություններում - Անահիտ Հրաչիկի Մնացականյան (ՀՀ ԳԱԱ հրատ.)
Обьектом исследования в сфере учета состояния, движения и эффективности использования ресурсов фактора труда на предприятии является совокупность наемныx работников, или персонал. Предприятие как самостоятельно xозяйствующий агент рынка имеет возможность самостоятельно распоряжаться своими ресурсами. Однако следует учитывать, что в полной мере предприятию принадлежат только ресурсы капитала, представленные в форме активов, так как ресурсы труда приципиально отличаются тем, что они неотделимы от своего собственника.The object of study on the state of utilization of workforce (including retaining) and performance evaluation in enterprises is a combination of paid and/or hired workforce or aggregate of hired employees or staff. The company, as an independently acting economic agent, is free to decide how to manage its resources. However, it needs to be taken into account that an enterprise fully owns only financial assets, and the workforce is an integral part of ownership and/or cannot be distinguished from the owner and that explains the difference between the financial asset and workforce.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ